An investigation of hydrogen embrittlement of 12Cr2Mo1R(H) steel by slow strain rate tests and first-principles calculation. Issue 6 (24th September 2020) - Kang, Qin; Fan, Yicheng; Zhang, Kun; Chen, Xiaolang; San, Hongyu; Chen, Yiqing; Zhao, Heming
Abstract : Purpose: With excellent mechanic properties and hydrogen embrittlement (HE) resistance, 12Cr2Mo1R(H) steel is suitable to make hot-wall hydrogenation reactors. However, longtime exposure to a harsh environment of high-pressure hydrogen at medium temperature in practical application would still induce severe hydrogen uptake and eventually damage the mechanical properties of the steel. The study aims to evaluate the HE resistance of the steel under different tensile strain rates after hydrogen charging and analyze the hydrogen effect from atomic level. Design/methodology/approach: This research studied the HE properties of 12Cr2Mo1R(H) steel by slow strain rate tests. Meanwhile, the effect of hydrogen on the structures and the mechanical properties of the simplified models of the steel was also investigated by first-principle calculations. Findings: Experimental results showed that after hydrogen pre-charging in this work, hydrogen had little effect on the microstructure of the steel. The elongations and reduction of cross-sectional area of the samples reduced a lot, by contrast, the yield and tensile strengths changed slightly. The 12Cr2Mo1R(H) steel was not very susceptible to HE with a maximum embrittlement index of about 20.00%. First principles calculation results showed that after H dissolution, lattice distortion occurred and interstitial H atoms would preferentially occupy the tetrahedral interstitial site in bcc-Fe crystal and increase the stability of the supercells. With the increase of H atoms added into the simplified model, the steel still possessed a good ductility and toughness at a low hydrogen concentration, while the material would become brittle as the concentration of hydrogen continued to increase. Originality/value: These finds can provide valuable information for subsequent HE studies on this steel.